Quality awards and market reactions: The case of Malaysia / Hasnizahanim Masilan - Masilan, Hasnizahanim (2007)
The purpose of this study is to identify the effect of quality award announcement the stock performance in Malaysia from the year Of 1996 until 2006, Quality Management Excellence Award (QMEA) has beet' chosen as the type Of quality award. Three methodologies are this study consists Of Event Study Methodology, Capital Assets pricing Model (CAPM) and & Jensen'S Index, The data used in this study consist of the data Bursa Malaysia Composite Index (BMCI), Treasury Dills, of stocks and also daily closing prices of companies Winning the Quality Management Excellence Award (QMEA) from year Of 1996 until 2006, It was found that results were consistent with findings of previous researches, suggesting the absence of abnormal returns for winner companies. The evidence suggests that the stock market is semi-strong efficient with respect to effect announcement of winning the Quality Management Excellence Award (QMEA) on its recipients.